Study on the Grain Boundary Misorientation Change and Texture Evolution in SUS304 Austenitic Stainless Steel at Low Cold‐Rolling Reductions. Issue 9 (31st May 2021) - Li, Junchen; Huang, Yaping; Pei, Weiyang; Zhao, Dejiang; Shi, Xulin
Abstract : To study the grain boundary misorientation change and texture evolution in austenitic stainless steel at low cold‐rolling reductions, SUS304 austenitic stainless steel samples with a cold‐rolling reduction of 5%, 8%, 10%, 15%, 20%, and 23% are prepared. The electron backscatter diffraction analysis reveals that with the increase in the cold‐rolling reduction, the proportions of low‐angle grain boundary (LAGB) and high‐angle grain boundary (HAGB) gradually increase and decrease, respectively. The decrease in HAGB reduces the toughness of the material. With the increase in cold‐rolling reduction, the strain area inside the material increases, which enhances the toughness and strength of the steel plate. Austenite textures at different cold‐rolling reductions are composed of Brass, Goss, S, and shear texture 011<122>. The intensity of the Brass‐type texture increases with the increasing cold‐rolling reduction. The martensite texture mainly consists of R‐Cube, Brass, shear texture 111<110>, 111<112>, and 332<113>. When the cold‐rolling reduction is less than 15%, the Brass texture appears in the α ′‐martensite phase. In addition, the intensity of the R‐Cube texture increases with the increasing cold‐rolling reduction. The martensite phase texture is affected by the austenite phase texture, and its formation can be attributed to the Kurdjumov–Sachs orientation relationship. Abstract : The martensite phase texture is affected by the austenite phase texture, and the formation of the martensite texture can be attributed to the Kurdjumov–Sachs orientation relationship. It is found, for the first time, that when the cold‐rolling reduction is less than 15%, the Brass texture appears with high intensity in the α ′‐martensite phase.